Under the vines. Series 2 [videorecording (DVD)] - White, Erin (Under the vines [DVD videorecording], 2023)
"After jointly inheriting a struggling vineyard in southern New Zealand, Sydney socialite Daisy Monroe and ex-London lawyer Louis Oakley are now trying to run it." --